Transposable elements as a potential source for understanding the fish genome - Ferreira, Daniela Cristina [UNESP]; Porto-Foresti, Fábio [UNESP]; Oliveira, Claudio de [UNESP]; Foresti, Fausto [UNESP] (Taylor & Francis, 2011)
Transposable elements are repetitive sequences with the capacity to move inside of the genome. They constitute the majority of the eukaryotic genomes, and are extensively present in the human genome, representing more than 45% of the genome sequences. The knowledge of the origin and function of these elements in the fish genome is still reduced and fragmented, mainly with regard to its structure and organization in the chromosomes of the representatives of this biological group, with data currently available for very few species that represent the great variety of forms and existing diversity. Comparative analyses ascertain differences in the organization of such elements in the species studied up to the present. They can be part of the heterochromatic regions in some species or be spread throughout the genome in others. The main objective of the present revision is to discuss the aspects of the organization of transposable elements in the fish genome.
Keywords: Fish; Genome; Transposon; Retrotransposons; Fluorescent in situ hybridization; Heterochromatin